Diagnosing and treating Enquiry Based Learning fatigue in Graduate Entry Nursing students. (January 2018) - Stacey, Gemma; Wilson, Claire; Reddy, Helen; Palmer, Chris; Henderson, James; Little, Hannah; Bull, Heather
Abstract: The use of student directed study approaches such as Enquiry Based Learning (EBL) in the design and implementation of Graduate Entry Nursing Circular is well established. The rational relates to the maximisation of graduate attributes such as motivation to learn, the ability to identify, search and assimilate relevant literature and the desire to take ownership of the direction and pace of learning. Existing alongside this however, is the observation that students remain under confident in the application of knowledge to a clinical context and frustrated with learning approaches which do not appear directly related to improving their competence in this area. We suggest the result of this is a gradual disengagement and dissatisfaction the learning forum amongst students and faculty, which we have defined as EBL fatigue. The symptoms and consequences of EBL fatigue amongst students and faculty are discussed alongside strategies which we suggest may act as preventative measures in reducing the risk of a local epidemic.